2008
DOI: 10.1177/105382590703000304
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of a Service-Learning Project: Students' Expectations, Concerns, and Reflections

Abstract: A qualitative analysis of written reflective assignments during a service-learning project at a Southeastern university provide insight into students' learning, as well as a means of assessing the experience for student growth and change. Expectations and concerns of students prior to the project were compared with postexperience reflections to identify changes as a result of their participation. Among student concerns were building relationships and rapport, confidence, and skills; expectations included pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…It was clear how much these graduates valued and benefitted from their personal service learning experience(s): Many students also perceived an academic benefit from their participation in service learning in that they said it helped to learn and remember the materials. This is similar to the findings of McClam et al (2008) where "one student wrote [in his/her journal], I learned more…by emersion into the field than I could have learned sitting in a classroom for four years" (p. 242). Academic benefits are most often viewed as short-term benefits, i.e., for the particular class the experience was in and in the rest of the participants' program.…”
Section: The Experience Is Very Valuable -Feels Good To Volunteer In supporting
confidence: 76%
See 1 more Smart Citation
“…It was clear how much these graduates valued and benefitted from their personal service learning experience(s): Many students also perceived an academic benefit from their participation in service learning in that they said it helped to learn and remember the materials. This is similar to the findings of McClam et al (2008) where "one student wrote [in his/her journal], I learned more…by emersion into the field than I could have learned sitting in a classroom for four years" (p. 242). Academic benefits are most often viewed as short-term benefits, i.e., for the particular class the experience was in and in the rest of the participants' program.…”
Section: The Experience Is Very Valuable -Feels Good To Volunteer In supporting
confidence: 76%
“…In fact, similar to research by McClam, Diambra, Burton, Fuss, & Fudge (2008) Further, the graduates developed skills that helped to prepare them to become teachers. This supports the work of Joseph et al (2007) where the students indicated that they believed their experience "prepar[ed] them for the job market" (p. 331).…”
Section: The Experience Is Very Valuable -Feels Good To Volunteer In mentioning
confidence: 99%
“…Butin (2006) further found that in service-learning the process of assessment is very complicated due to absence of well articulated criteria. In this regard, some writers have found that certain assessment mechanisms are missing to evaluate the outcomes related to participation in service-learning (McClam, Diambra, Burton, Fuss, & Fudge, 2008). There is no assessment of many service-projects either because teachers have less know-how of how to assess or they have to wait until the servicelearning activity or project is completed (Speck & Hoppe, 2004).…”
Section: Students' Community Awarenessmentioning
confidence: 99%
“…It allows the learners to adopt multifaceted ways for development and personal growth. It also impacts the construction of knowledge and develops effective habits of mind (McCaugherty, 1991;McClam, Diambra, Burton, Fuss, & Fudge, 2008). Apart from being a high level cognitive experience, reflection is also an emotional experience in which learners think critically and get involves in the experience more enthusiastically (Moffat & Decker, 2000).…”
Section: Importance Of Reflectionmentioning
confidence: 99%
“…Some writers have concluded that for meaningful learning, structured thinking provides the foundation which can be done through reflection. This may contribute towards not only improving the service-behaviour but also learning (Felten et al, 2006;McClam et al, 2008).…”
Section: Reflection and Learningmentioning
confidence: 99%